The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/sym11020157
|View full text |Cite
|
Sign up to set email alerts
|

Face Recognition with Symmetrical Face Training Samples Based on Local Binary Patterns and the Gabor Filter

Abstract: In the practical reality of face recognition applications, the human face can have only a limited number of training images. However, it is known that, in general, increasing the number of training images also increases the performance of face recognition systems. In this case, a new set of training samples can be generated from the original samples, using the symmetry property of the face. Although many face recognition methods have been proposed in the literature, a robust face recognition system is still a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The most general definition of the coefficient of determination is Table 2 shows the specifications of the layer that is used in deep learning. [56] 75.12% CRC [69] 79.4% Gabor wavelet with Euclidian method [57] 83.44% Symmetrical face sample method [49] 81.43% Proposed method 85.25%…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…The most general definition of the coefficient of determination is Table 2 shows the specifications of the layer that is used in deep learning. [56] 75.12% CRC [69] 79.4% Gabor wavelet with Euclidian method [57] 83.44% Symmetrical face sample method [49] 81.43% Proposed method 85.25%…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…• Wavelet transform and GLCM 142,143 • Binary Gabor filter 144 • SVD and DWT transform 145 • Gabor filter and GLCM 146…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results showed that the proposed method yields excellent performance compared with several conventional methods from literature. Allagwail et al [32] presented a two-dimensional discrete wavelet transform based on the local binary pattern for face recognition using a symmetry. The introduced method has three main stages: preprocessing, feature extraction and classification.…”
Section: Related Workmentioning
confidence: 99%